The procedural principle of immediacy in virtual hearings in Colombia - España-Toro, Angie Paola (Scientific journal of social studies, 2023)
During the years 2020 - 2021, our society faced a health emergency arising from the Covid-19 virus, creating a procedural legal approach to the application of different technological tools regulated by ICT (Information and Communication Technologies) within the Public hearings in Colombia, which there was little knowledge. That is why the following legal question arises: how is the protection of the procedural principle of immediacy generated in virtual hearings in Colombia? In response, both the doctrine and the Colombian law will be considered, presenting as starting points the analysis carried out to article 107 of the General Code of Process (law 1564 of 2012), which establishes rules for the application of hearings, giving I go on to identify the procedural principle of immediacy within them, through different concepts and protection mechanisms necessary in order to reach the conclusion.
Keywords: Digital justice; procedural principle of immediacy; technology in the administration of justice; virtual audiences